Fairy-tale therapy as a way to combat phobias - T. S. Gordon (Вестник университета)
The article considers the fairy-tale therapy as one of the most effective methods to combat phobias and anxiety in primary school age. The author analyses the main aspects of the fairy-tale work, studies its forms, provides examples of creative thinking of primary school pupils, helping to overcome fear and anxiety. Connecting the mind and imagination of a younger schoolboy, the fairy tale helps him find ways and ways to get rid of phobias, aggression and anxiety. The article considers the fairy tale as a tool that presents algorithms for solving specific problems or conflict situations, the consequences of circumstances with a concentrated component of low-frequency emotions, as well as a way to give strength to further fight against fears or even annihilating them. The paper also reviews four types of fairy tales used in therapeutic activities with younger pupils, which have a different mechanism of psychological influence.